A Study of COVID-19 News Headline Strategies on Thairath Online and Matichon Online - Yolai, Rittisak; Hannapha, Pakphoom (Journal of Buddhist Education and Research (JBER), 2025)
This research article aimed to examine the headline strategies employed in online news coverage of COVID-19 by Thairath Online and Matichon Online. The sample consisted of 160 news articles published between February 1 and May 31, 2020. A data recording form was utilized as the research instrument. The findings revealed that both news outlets employed thirteen distinct headline characteristics, though with varying frequencies. For Thairath Online, the distribution included slang (32 instances), quotations (29), celebrity/nickname/informal and formal names (30), abbreviations (23), professions (12), organizational names (16), loanwords (41), strong/harsh words (5), emotionally charged words (25), emotive or attention-grabbing punctuation (15), keywords (56), proverbs/phrases/idioms (64), and numerical references (60). Similarly, Matichon Online employed slang (26 instances), quotations (40), celebrity/nickname/informal and formal names (28), abbreviations (25), professions (16), organizational names (36), loanwords (38), strong/harsh words (4), emotionally charged words (28), emotive or attention-grabbing punctuation (16), keywords (48), proverbs/phrases/idioms (60), and numerical references (60).